2018
DOI: 10.1109/lra.2018.2853640
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-Based Customization of Bending Modalities for 3D-Printed Soft Pneumatic Actuators

Abstract: In this work, we propose a novel type of 3D-printed soft pneumatic actuator that allows geometry-based customization of bending modalities. While motion in the 3Dspace has been achieved for several types of soft actuators, only 2D-bending has been previously modelled and characterized within the scope of 3D-printed soft pneumatic actuators. We developed the first type of 3D-printed soft pneumatic actuator which, by means of the unique feature of customizable cubes at an angle with the longitudinal axis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In pneumatic bending actuators (pneunets), which produce bending by inflating a series of chambers about an inextensible membrane, parametric studies have investigated the relationship between the chamber dimensions and performance. [ 59–62 ] Using FEA and experimental methods, they found increasing surface area of pneumatic chambers and reducing their wall thickness increases bending. [ 28,63,64 ] However, chamber shape was not a significant determinant of bending as semicircular, square, and triangular chambers all produced similar pressure‐bending relationships.…”
Section: Model‐based Design Optimizationmentioning
confidence: 99%
“…In pneumatic bending actuators (pneunets), which produce bending by inflating a series of chambers about an inextensible membrane, parametric studies have investigated the relationship between the chamber dimensions and performance. [ 59–62 ] Using FEA and experimental methods, they found increasing surface area of pneumatic chambers and reducing their wall thickness increases bending. [ 28,63,64 ] However, chamber shape was not a significant determinant of bending as semicircular, square, and triangular chambers all produced similar pressure‐bending relationships.…”
Section: Model‐based Design Optimizationmentioning
confidence: 99%
“…The authors reported an average wall thickness of 0.64 mm. The low-cost SPA was 3D/4D-printed using the FDM technique and commercially available thermoplastic poly(urethane) (TPU), NinjaFlex (NinjaTek, PA) filament (Rosalia, Ang, and Yeow 2018;Yap, Ng, and Yeow 2016). The complex inner features without any supporting materials were utilized to devise the actuator with high force tip performance up to 80 N (Yap, Ng, and Yeow 2016).…”
Section: Fabrication Of 4d-printed Bending-type Soft Pneumatic Actuatorsmentioning
confidence: 99%
“…It was reported that the model and value of 10 could not predict the behavior of SPAs with low deflections while the results were more accurate for bending angles more than 130°. A 3 rd order Yeoh model was also successfully implemented for the bending modeling of TPU made 3D/4D-printed SPA (Rosalia, Ang, and Yeow 2018). Different material models, including Mooney-Rivlin, Neo-Hookean, and Ogden were developed to obtain maximum consistency with experimental results of an additively manufactured SPA made of TPU (Dilibal, Sahin, and Celik 2018).…”
Section: Energy Model Formulamentioning
confidence: 99%
“…However, Young's modulus alone cannot refer to the performance of rubber accurately. Usually, property of rubber was expressed with multiple parameters according to different constitutive models [21,29]. Therefore, the property of Dragon Skin 30 should be calibrated.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…With high material nonlinearity and deformation nonlinearity, it is difficult for pneumatic actuator to achieve accurate analytical solution. FEM is a common analysis method with high accuracy for soft robot [18,29]. Through FEM simulation, input and output characterization of the CBAs and the FBAs can be acquired, which can be used for structure improvement and parameter optimization.…”
Section: A Fem Modellingmentioning
confidence: 99%